Establishment and implementation of China's civil service system - Xu Zhenuhan (1996)
Since the Provisional Regulations on Civil Servants came into force on 1 October 1993, the establishment and the implementation of China's civil service system has been smoothly under way. This paper provides information on the reform process and the experiences that have been accumulated. With a view to meeting the requirements of a socialist market economy and modernization, China's Civil Service system underwent a gradual reform of the cadre personnel system. After the founding of new China, a personnel management system was established to meet the requirements of the centralized planning economy. The overall planning and management of the country's human resources was carried out by the state through administrative means. The managing staff in enterprises and institutions and technical workers were all defined as cadres. This management system played a positive role in consolidating the newly established state power, implementing the unification of politics and economy and focusing efforts on key reconstruction matters. With the transfer of the state's key tasks and the implementation of economic reform, it became more and more difficult for the personnel management system to meet the requirements of reform. Consequently, a new Civil Service system with Chinese characteristics has been formulated, with foreign experiences serving as a reference point and traditional merit factors and many years of practice and exploration taken into account. - Reproduced
Keywords: Civil service - China; Civil service